A Single Dose of 5-MeO-DMT Stimulates Cell Proliferation, Neuronal Survivability, Morphological and Functional Changes in Adult Mice Ventral Dentate Gyrus - Lima da Cruz, Rafael Vitor; Moulin, Thiago C.; Petiz, Lyvia Lintzmaier; Leão, Richardson N. (Frontiers in Molecular Neuroscience, 2018)
The subgranular zone of dentate gyrus (DG) is one of the few regions in which neurogenesis is maintained throughout adulthood. It is believed that newborn neurons in this region encode temporal information about partially overlapping contextual memories. The 5-Methoxy-N,N-dimethyltryptamine (5-MeO-DMT) is a naturally occurring compound capable of inducing a powerful psychedelic state. Recently, it has been suggested that DMT analogues may be used in the treatment of mood disorders. Due to the strong link between altered neurogenesis and mood disorders, we tested whether 5-MeO-DMT is capable of increasing DG cell proliferation . We show that a single intracerebroventricular injection of 5-MeO-DMT increases the number of BrdU+ cells in adult mice DG. Moreover, using a transgenic animal expressing tamoxifen-dependent Cre recombinase under doublecortin promoter, we found that 5 Meo-DMT treated mice had a higher number of newborn DG Granule cells (GC)We also showed that these DG GC have more complex dendritic morphology after 5-MeO-DMT. Lastly, newborn GC treated with 5-MeO-DMT, display shorter afterhyperpolarization potentials and higher action potential threshold compared. Our findings show that 5-MeO-DMT affects neurogenesis and this effect may contribute to the known antidepressant properties of DMT-derived compounds.